The High Glacial (LGP, LGM, MIS 3-2) southern outlet glaciers of the Tibetan inland ice through Mustang into the Thak Khola as further evidence of the Tibetan ice - Kuhle, M. (Journal of Nepal Geological Society, 2011)
Available with full text.